From ornament to total design: a historic overview from Hal Foster (Palíndromo, 2020)
This paper takes up Hal Foster’s controversial “Design and Crime” to outline a brief historical overview of the relationship between Art Nouveau ornamentation and what the author calls “total design”. To this end, I revisit the nineteenth-century debate about ornament and explain how the cult of personality emerges with the ornamentation of public life. From this, I argue that the diffusion of design in contemporary life is linked to the behavior of the “designer of yourself”. Finally, I point out that Foster’s provocation remains current, indicating that, contrary to the narratives that expose design as the overcoming of ornament, design continues to operate largely as an ornamental rationality.
Keywords: Hal Foster; Ornament; Total Design; Art Nouveau